IMPLEMENTASI GOOD CORPORATE GOVERNANCE PADA PONDOK PESANTREN SEBAGAI UPAYA PENINGKATAN DAYA SAING - Oktafia, Renny; Basith, Abdul (Jurnal Ekonomi Islam, 2017)
This study aims to describe the implementation of the principles of good corporate governance at the Pondok Pesantren Al-Fattah, Sidoarjo. The method used to determine the informant is purposive sampling. In this qualitative research data collection using interviews, documentation and observation. From these results, it can be concluded that the implementation of the principles of good corporate governance in Pondok Pesantren As-Shafiites good enough. This is evidenced by the development of cottage pesntren which is constantly increasing. Suggestions for boarding is better optimize the principle of independency for the success of future schools.